Cerebral perfusion responses to active standing are attenuated in patients with vasovagal syncope. (24th May 2021) - Perez-Denia, L; Claffey, P; O"reilly, A; Delgado-Ortet, M; Rice, C; Kenny, RA; Finucane, C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Irish Research Council (IRC): Government of Ireland Postgraduate Scholarship Programme 2018, Dublin, Ireland Fundació Universitària Agustí Pedro i Pons, Universitat de Barcelona, Barcelona, Spain Background: Syncope is a transient loss of consciousness due to cerebral hypoperfusion. While traditionally peripheral haemodynamics are monitored during clinical assessment of syncope, relatively little is known about cerebrovascular haemodynamics during orthostasis in patients with syncope. Purpose: Here we investigated whether young patients with syncope present an altered cerebral perfusion when compared to healthy controls. Given potential hyper-reactivity of the autonomic nervous system previously reported in these patients, we hypothesise that an overly active cerebral autoregulation will be present in patients with syncope. Methods: Consecutive patients were prospectively recruited from a National Falls and Syncope Unit, and a convenience sample of young healthy community dwelling adults was recruited from a local university (16-30 years). Participants performed a 3 minute active stand test with continuous measurement of beat-to-beat peripheral haemodynamics (blood pressure (BP), heart rate (HR)) and changes in concentration of oxygenated Δ[O2Hb] and deoxygenated Δ[HHb] haemoglobin were derived from a near-infrared spectroscopy (NIRS) monitor. Baseline, steady state and other time domain features were derived for Δ[O2Hb] (nadir, overshoot, overshoot-to-nadir, overshoot-to-nadir recovery rate) and Δ[HHb] (peak, trough, peak-to-trough, peak-to-trough recovery rate) and multiple linear regression was used to compare differences between the two groups correcting for covariates (p < 0.05 significant). Results: Patients (n = 40) were younger (20(5.5) vs 23(1) years, p = 0.003) than controls (n = 17) and were well matched in gender, weight, height, BMI and resting haemodynamics. Patients had a smaller Δ[O2Hb] overshoot-to-nadir difference (β: -0.749, CI:(-1.593 0.094), p = 0.08), a slower Δ[O2Hb] recovery rate (β: -0.186, CI:(-0.388 0.016), p = 0.071), and smaller Δ[HHb] peak-to-trough difference (β: -0.530, CI:( -0.921 0.138), p = 0.018) and slower Δ[HHb] recovery rate (β: -0.151, CI: (0.244 0.057), p = 0.008). Conclusion: Patients with syncope had signs of an attenuated cerebral oxygenation response to an AS when compared to controls. We hypothesise that this is due to hyper-reactive cerebral autoregulation mechanism, which might be related to a hyper-sensitive autonomic system. Furthering our understanding of vasovagal syncope physiology can help inform future interventions and treatments. This study shows the clinical value of measuring cerebral perfusion using NIRS, an easy to use and readily applicable tool, in the assessment of syncope.